Land Stability at The Final Closing of Waste Final Disposal Supit Urang in Malang City - Yustika Aristya Widyasari; I.D.A.A Warmadewanthi; Putu Tantri Kumala Sari (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
Amount of waste that enters waste final disposal (TPA) Supit Urang is 833.625 m3/day, with a gradual pile pattern up to ± 12 meters. From 2018 until 2020, new cell was being established. On 13th July 2018, landslide hit the active cell area so that it was necessary to close the landfill zone at the TPA. Based on this background, it is necessary to calculate the landfill stability in landfill management until the new cell is done. The stability calculation also anticipates the subgrade strength and remaining waste cell capacity. Research method was carried out by observing the amount of incoming waste, characteristics of waste at the TPA, topography measurement and the results of observations of subgrade strength. In determining the calculation of land stability analysis, Geo 5 program was used. For technical data, topographic measurement was conducted directly at the TPA and compared with existing topography obtained from secondary data. Based on the topography result, it will be determined the contour slice in the field and a total slice of landfill plan. The result of this study shows that the landfill stability depends on subgrade type and landfill structuring at the TPA.